BaTiO3 ferroelectric film with high energy storage at low temperature and method and application thereof

By preparing BaTiO3 ferroelectric film at low temperature 200°C and using LaNiO3 target to deposit the buffer layer, the problem of low energy storage efficiency of barium titanate film in the prior art is solved, high energy storage efficiency and high energy storage density are achieved, and compatible with the CMOS-Si process.

CN119506779APending Publication Date: 2025-02-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646893.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the energy storage efficiency of barium titanate films prepared at 200°C at the in-situ method is poor and cannot meet the application requirements. The impact of buffer layer thickness on the performance of BaTiO3 ferroelectric film has not been explored.

Method used

The BaTiO3 ferroelectric film was prepared by the steps of substrate treatment, deposition of the bottom electrode, buffer layer, barium titanate dielectric layer and top electrode using the LaNiO3 target material to deposit the buffer layer by radio frequency or DC magnetron sputtering at 195-205°C. The total film thickness of the buffer layer is 0-50 nm.

Benefits of technology

The BaTiO3 ferroelectric film with high energy storage efficiency and high energy storage density has a large dielectric constant and low dielectric loss, and the energy storage efficiency reaches 78.2%. It is prepared at a low temperature of 200℃, making it more compatible with the CMOS-Si process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506779A_ABST
    Figure CN119506779A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of thin film materials, and particularly provides a BaTiO3 ferroelectric thin film with high energy storage at low temperature and a method and application of the BaTiO3 ferroelectric thin film. The preparation method of the BaTiO3 ferroelectric film comprises the following steps: processing a substrate, depositing a bottom electrode on the substrate, depositing a buffer layer on the bottom electrode, depositing a barium titanate dielectric layer on the buffer layer, and depositing a top electrode on the barium titanate dielectric layer. The step of depositing the buffer layer on the bottom electrode comprises the following steps of: adopting a LaNiO3 target material, keeping the temperature at 200 DEG C, and depositing the buffer layer on the substrate in a radio frequency or direct current magnetron sputtering mode; and the total film thickness of the buffer layer is 0-50nm. The problems that in the prior art, a barium titanate film prepared through an in-situ preparation method at the temperature of 200 DEG C is poor in performance, application requirements cannot be met, and the performance of a BaTiO3 ferroelectric film is regulated and controlled by the thickness of a buffer layer are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin film material preparation, and in particular relates to a BaTiO3 ferroelectric thin film with high energy storage at low temperature and a method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the development of society and the progress of science and technology, the demand for miniaturization and integration of devices is getting higher and higher. Ferroelectric materials, especially ferroelectric thin films, as an important type of raw material for functional devices in the modern electronic industry, have good ferroelectric, piezoelectric, pyroelectric and other properties, which make them have broad application prospects in the fields of microelectronics, optoelectronics and micro-electromechanical systems, and are one of the frontiers and hotspots of current scientific research. Among them, simple cubic perovskite-type ABO3 structure ferroelectric materials have high power density, excellent thermal stability and cycle stability, which makes them show wide application potential in the electronic industry and ceramic industry.

[0004] Barium titanate (BaTiO3, BTO for short) is a typical ferroelectric material with a simple cubic perovskite ABO3 structure. The ions at the A and B positions can be replaced by ions of different valences / radii alone or in combination (where the valence state of the A position ion is +2 or +1; the valence state of the B position ion is +4 or +5). Due to the complexity of the valence state and doping, the material presents a variety of structural and functional properties to meet the needs of different application fields.

[0005] In order to achieve compatibility with CMOS process, the inventors provided a method for preparing high energy storage density BaTiO3 ferroelectric film and its products and applications in previous studies. The preparation temperature of BaTiO3 ferroelectric film was reduced to 200°C, achieving good compatibility with CMOS process. However, the inventors found that the energy storage efficiency of the prepared barium titanate film was poor (at 200°C, the energy storage efficiency was 63%), which could not meet the application requirements, and the influence of buffer layer thickness on the performance of BaTiO3 ferroelectric film was not involved. Summary of the invention

[0006] In view of the fact that the barium titanate film prepared by the in-situ method at 200°C in the prior art has poor energy storage efficiency and cannot meet application requirements, and the effect of the buffer layer thickness on the performance of the BaTiO3 ferroelectric film has not been explored, the present invention provides a low-temperature high-energy storage BaTiO3 ferroelectric film and a method and application thereof. At a low temperature of 200°C, the preparation of a BaTiO3 ferroelectric film with high energy storage efficiency and high energy storage density is achieved simultaneously, and the BaTiO3 ferroelectric film also has a large dielectric constant and low dielectric loss.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] On the one hand, the present invention provides a method for preparing a BaTiO3 ferroelectric thin film with high energy storage efficiency at low temperature, comprising the following steps: substrate treatment, depositing a bottom electrode on the substrate, depositing a buffer layer on the bottom electrode, depositing a barium titanate dielectric layer on the buffer layer, and depositing a top electrode on the barium titanate dielectric layer;

[0009] Depositing a buffer layer on the bottom electrode comprises the following steps: using a LaNiO3 target material, maintaining the temperature at 195-205°C to deposit the buffer layer on the substrate by radio frequency or direct current magnetron sputtering;

[0010] The total film thickness of the buffer layer is 0 to 50 nm.

[0011] Preferably, the total thickness of the buffer layer is 25 to 50 nm.

[0012] In a second aspect, the present invention provides a BaTiO3 ferroelectric film with high energy storage at low temperature obtained by the above-mentioned preparation method.

[0013] In a third aspect, the present invention provides the application of the above-mentioned BaTiO3 ferroelectric film with high energy storage at low temperature in energy storage.

[0014] Preferably, the energy storage includes an electronic chip or an integrated device.

[0015] The beneficial effects of the present invention are:

[0016] (1) The present invention adopts the low-temperature in-situ preparation of BaTiO3 thin film as nano-columnar crystal. From the structural point of view, the barium titanate nano-columnar crystal structure prepared by the present invention is obvious and the lanthanum nickel oxide buffer layer has obvious effect. According to electrical tests, the obtained film has excellent ferroelectric properties and energy storage characteristics, and has high energy storage efficiency and high energy storage density. Specifically, its residual polarization intensity is 5.9μC / cm 2 , saturation polarization intensity 61.7μC / cm 2 , field-induced polarization up to 55.8μC / cm 2 The breakdown field strength is 4.0MV / cm, and the effective energy storage density is as high as 94.7J / cm 3 , the energy storage efficiency is 78.2%.

[0017] (2) The BaTiO3 film prepared at low temperature in the present invention also has a large dielectric constant and low dielectric loss, ensuring its excellent charging and energy storage performance.

[0018] (3) BaTiO3 is a green, environmentally friendly, lead-free ferroelectric ceramic material with simple elemental composition.

[0019] (4) The present invention is prepared under low temperature conditions of 200° C., has stronger operability, and is more compatible with CMOS-Si technology.

[0020] (5) The BaTiO3 thin film prepared by the magnetron sputtering method of the present invention has the advantages of good density, strong adhesion to the substrate, high flatness, and is conducive to industrial promotion.

[0021] (6) The BaTiO3 thin film buffer layer prepared by the present invention is an ABO3 type perovskite material LaNiO3, which better matches the BaTiO3 lattice and guides the BaTiO3 thin film to grow into nano-columnar crystals. By adjusting the thickness of LaNiO3, the orientation and electrical properties of the thin film are optimized.

[0022] (7) After the parameters are improved, the residual polarization is greatly reduced and the energy storage efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 Schematic diagram of the principle of the preparation method used in the embodiment of the present invention;

[0025] Figure 2 Schematic diagram of the structure of the barium titanate thin film system prepared in the embodiment of the present invention, Si single crystal substrate, Pt / Ti bottom electrode, lanthanum nickelate buffer layer, barium titanate thin film, gold top electrode, wherein the diameter of the gold top electrode can be 200μm to 1000μm, and the electrical test of connecting the Pt / Ti bottom electrode and the gold top electrode;

[0026] Figure 3 The XRD (a) and GIXD (b) diagrams of the barium titanate film prepared in the embodiment of the present invention;

[0027] Figure 4 is a SEM image of the barium titanate film prepared in Example 1 of the present invention;

[0028] Figure 5 The dielectric constant (a) and loss tangent (b) of the barium titanate film prepared in the embodiment of the present invention are shown;

[0029] Figure 6 This is a unilateral hysteresis loop of the barium titanate film prepared in Example 1 of the present invention;

[0030] Figure 7 This is a unilateral hysteresis loop of the barium titanate film prepared in Example 2 of the present invention;

[0031] Figure 8 This is a unilateral hysteresis loop of the barium titanate film prepared in Example 3 of the present invention;

[0032] Fig. 9 This is the unilateral hysteresis loop of the barium titanate film prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The barium titanate film prepared by the in-situ method at 200°C in the prior art has poor energy storage efficiency and cannot meet application requirements, and the problem of the influence of the buffer layer thickness on the performance of the BaTiO3 ferroelectric film is solved.

[0034] In a typical embodiment, the present invention provides a method for forming a BaTiO3 ferroelectric thin film with high energy storage efficiency at low temperature, comprising the following steps: substrate treatment, depositing a bottom electrode on the substrate, depositing a buffer layer on the bottom electrode, depositing a barium titanate dielectric layer on the buffer layer, and depositing a top electrode on the barium titanate dielectric layer;

[0035] Depositing a buffer layer on the bottom electrode comprises the following steps: using a LaNiO3 target material, maintaining the temperature at 195-205°C to deposit the buffer layer on the substrate by radio frequency or direct current magnetron sputtering;

[0036] The total film thickness of the buffer layer is 0 to 50 nm.

[0037] Preferably, the temperature for depositing the buffer layer is 200°C.

[0038] In some examples of this implementation mode, the total film thickness of the buffer layer is 25-50 nm. The total film thickness of the buffer layer has a great influence on the energy storage efficiency and energy storage density at a low temperature of 200°C.

[0039] The advantages of magnetron sputtering for preparing thin films are as follows: 1) high efficiency; 2) high density; 3) strong adhesion to the substrate; 4) good film flatness. Figure 1 As shown: Under the action of the electric field E, the electrons collide with argon atoms in the process of flying to the substrate, ionizing them into Ar + And a new electron is generated. The electron flies to the substrate, and Ar + The atoms on the target surface absorb Ar +The kinetic energy of the target material breaks away from its lattice constraints, escapes from the surface of the target material and flies to the substrate, and is deposited on the substrate to form a thin film. Magnetron sputtering can be used to prepare a variety of thin film materials, such as metal films, ceramic films, polymer films, composite films, etc. There are many factors (such as gas flow, target power, temperature, coating atmosphere, etc.) that can affect the quality of magnetron sputtering films, so various process parameters should be controlled during the coating practice to improve the uniformity of the film and optimize its physical properties.

[0040] In some embodiments of this implementation mode, the substrate treatment includes the following steps: selecting a semiconductor substrate Si or Si / SiO2 as a substrate, ultrasonically cleaning it with an ultrasonic detergent to remove oily impurities, and removing the ultrasonic detergent with deionized water, then drying it with an inert gas, and finally placing it in a vacuum coating chamber to evacuate it.

[0041] Further, the ultrasonic detergent is acetone, alcohol or a mixture of the two, preferably a mixture of acetone and alcohol;

[0042] Furthermore, the inert gas is nitrogen;

[0043] Furthermore, the vacuum coating chamber includes the following steps: the backing vacuum is pumped to 1.9×10 -4 -2×10 -4 Pa, heated to 290-300℃.

[0044] In some examples of this embodiment, depositing a bottom electrode on a substrate comprises the following steps: using a conductive metal target material Ti / Pt, depositing a bottom electrode layer on the substrate by radio frequency or direct current magnetron sputtering at a temperature during substrate treatment.

[0045] Furthermore, the atmosphere during deposition was Ar.

[0046] Furthermore, the Ar gas flow rate is controlled at 35-40 sccm.

[0047] Furthermore, the air pressure is controlled at 0.3-0.35Pa.

[0048] Further, the target power is 50-55W.

[0049] Furthermore, the total film thickness of the bottom electrode is 100-150 nm.

[0050] In some examples of this embodiment, during the process of depositing the buffer layer on the bottom electrode, the atmosphere during the deposition is a mixed gas of Ar and O2;

[0051] Furthermore, the gas pressure of the deposited buffer layer is controlled to be ≤0.3Pa, preferably 0.3Pa.

[0052] Furthermore, the Ar gas flow rate is controlled at 50-60 sccm, and the O2 flow rate is controlled at 15-20 sccm.

[0053] Further, the target power is 90-100W.

[0054] In some examples of this embodiment, depositing a barium titanate dielectric layer on the buffer layer includes the following steps: using a ceramic BaTiO3 target and maintaining the temperature of depositing the buffer layer to deposit a BaTiO3 layer on the buffer layer by radio frequency magnetron sputtering.

[0055] Furthermore, the gas pressure for depositing the barium titanate dielectric layer is ≥1.2Pa, preferably 1.2Pa.

[0056] Furthermore, the sputtering atmosphere is a mixed gas of Ar and O2.

[0057] Furthermore, the Ar gas flow rate is controlled at 50-60 sccm, and the O2 flow rate is controlled at 15-20 sccm.

[0058] Furthermore, the sputtering power of the BaTiO3 target is 100W.

[0059] Furthermore, the thickness is 250nm to 350nm.

[0060] In some embodiments of this embodiment, depositing the top electrode on the barium titanate dielectric layer includes the following steps: using a metal target, depositing by radio frequency or DC magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2 to 5 W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

[0061] In another typical embodiment, the present invention provides a BaTiO3 ferroelectric film with high energy storage at low temperature obtained by the above preparation method.

[0062] The breakdown field strength is 3-4MV / cm, and the effective energy storage density is 90-100J / cm 3 , the energy storage efficiency is 75-82%.

[0063] In another typical embodiment, the present invention provides the application of the above-mentioned BaTiO3 ferroelectric film with high energy storage efficiency at low temperature in energy storage.

[0064] Preferably, the energy storage includes electronic chips and integrated devices.

[0065] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0066] Example 1

[0067] (1) Matrix treatment:

[0068] Select semiconductor substrate Si or Si / SiO2 as the substrate, use acetone and alcohol to ultrasonically clean it to remove oily impurities on the surface, then use deionized water to clean it for the final time, then blow it dry with nitrogen, and finally put it into the vacuum coating chamber, and draw the back vacuum to 2×10 -4 Pa, heated to 300°C;

[0069] (2) Depositing the bottom electrode on the substrate

[0070] A conductive metal target material Ti / Pt is used, and a bottom electrode layer is deposited on the substrate by radio frequency or direct current magnetron sputtering at the temperature of step (1). The atmosphere during deposition is Ar, the Ar gas flow rate is controlled at 39 sccm, the gas pressure is controlled at 0.3 Pa, the target power is 55 W, and the total bottom electrode film thickness is 150 nm.

[0071] (3) Deposition of buffer layer on the bottom electrode

[0072] A LaNiO3 target material with a higher matching degree with tetragonal barium titanate is used, and the temperature is maintained at 200°C to deposit a buffer layer on the substrate by RF or DC magnetron sputtering. The atmosphere during deposition is a mixed gas of Ar and O2, the Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 0.3Pa, the target power is 100W, and the total film thickness of the buffer layer is 50nm.

[0073] (4) Deposition of a barium titanate dielectric layer on the buffer layer

[0074] A ceramic BaTiO3 target is used, and the temperature in step (3) is maintained to deposit a BaTiO3 layer on the bottom electrode by radio frequency magnetron sputtering. The sputtering atmosphere is a mixed gas of Ar and O2. The Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 1.2Pa, the sputtering power of the BaTiO3 target is 100W, and the thickness is 250-350nm.

[0075] (5) Deposition of top electrode on the barium titanate dielectric layer

[0076] Using metal targets, deposition is carried out by RF or DC magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2-5W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

[0077] After electrical performance testing, the ferroelectric loop Figure 6 As shown, from Figure 6It can be seen that the ferroelectric film obtained in this embodiment has excellent energy storage performance. After electrical testing (voltage 100V), the obtained film has excellent ferroelectric performance and energy storage characteristics, and its residual polarization intensity is 5.9μC / cm 2 , saturation polarization intensity 61.7μC / cm 2 , field-induced polarization up to 55.8μC / cm 2 The breakdown field strength is 4.0MV / cm, and the effective energy storage density is as high as 94.7J / cm 3 , the energy storage efficiency is 78.2%.

[0078] Example 2

[0079] (1) Matrix treatment:

[0080] Select semiconductor substrate Si or Si / SiO2 as the substrate, use acetone and alcohol to ultrasonically clean it to remove oily impurities on the surface, then use deionized water to clean it for the final time, then blow it dry with nitrogen, and finally put it into the vacuum coating chamber, and draw the back vacuum to 2×10 -4 Pa, heated to 300°C;

[0081] (2) Depositing the bottom electrode on the substrate

[0082] A conductive metal target material Ti / Pt is used, and a bottom electrode layer is deposited on the substrate by radio frequency or direct current magnetron sputtering at the temperature of step (1). The atmosphere during deposition is Ar, the Ar gas flow rate is controlled at 39 sccm, the gas pressure is controlled at 0.3 Pa, the target power is 55 W, and the total bottom electrode film thickness is 150 nm.

[0083] (3) Deposition of a barium titanate dielectric layer on the bottom electrode

[0084] A ceramic BaTiO3 target is used, and the temperature in step (3) is maintained to deposit a BaTiO3 layer on the bottom electrode by radio frequency magnetron sputtering. The sputtering atmosphere is a mixed gas of Ar and O2. The Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 1.2Pa, the sputtering power of the BaTiO3 target is 100W, and the thickness is 250-350nm.

[0085] (4) Deposition of top electrode on the barium titanate dielectric layer

[0086] Using metal targets, deposition is carried out by RF or DC magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2-5W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

[0087] After electrical performance testing, the ferroelectric loop Figure 7 As shown, from Figure 7It can be seen that the ferroelectric film obtained in this embodiment has excellent energy storage performance. After electrical testing (voltage 100V), the obtained film has excellent ferroelectric performance and energy storage characteristics, and its residual polarization intensity is 1.2μC / cm 2 , saturation polarization intensity 15.5μC / cm 2 , field-induced polarization up to 14.3μC / cm 2 The breakdown field strength is 4.0MV / cm, and the effective energy storage density is as high as 26.9J / cm 3 , the energy storage efficiency is 81.3%.

[0088] Example 3

[0089] (1) Matrix treatment:

[0090] Select semiconductor substrate Si or Si / SiO2 as the substrate, use acetone and alcohol to ultrasonically clean it to remove oily impurities on the surface, then use deionized water to clean it for the final time, then blow it dry with nitrogen, and finally put it into the vacuum coating chamber, and draw the back vacuum to 2×10 -4 Pa, heated to 300°C;

[0091] (2) Depositing the bottom electrode on the substrate

[0092] A conductive metal target material Ti / Pt is used, and a bottom electrode layer is deposited on the substrate by radio frequency or direct current magnetron sputtering at the temperature of step (1). The atmosphere during deposition is Ar, the Ar gas flow rate is controlled at 39 sccm, the gas pressure is controlled at 0.3 Pa, the target power is 55 W, and the total bottom electrode film thickness is 150 nm.

[0093] (3) Deposition of buffer layer on the bottom electrode

[0094] A LaNiO3 target material with a higher matching degree with tetragonal barium titanate is used, and the temperature is maintained at 200°C to deposit a buffer layer on the substrate by RF or DC magnetron sputtering. The atmosphere during deposition is a mixed gas of Ar and O2, the Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 0.3Pa, the target power is 100W, and the total film thickness of the buffer layer is 25nm.

[0095] (4) Deposition of a barium titanate dielectric layer on the buffer layer

[0096] A ceramic BaTiO3 target is used, and the temperature in step (3) is maintained to deposit a BaTiO3 layer on the bottom electrode by radio frequency magnetron sputtering. The sputtering atmosphere is a mixed gas of Ar and O2. The Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 1.2Pa, the sputtering power of the BaTiO3 target is 100W, and the thickness is 250-350nm.

[0097] (5) Deposition of top electrode on the barium titanate dielectric layer

[0098] Using metal targets, deposition is carried out by RF or DC magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2-5W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

[0099] After electrical performance testing, the ferroelectric loop Figure 8 As shown, from Figure 8 It can be seen that the ferroelectric film obtained in this embodiment has excellent energy storage performance. After electrical testing (voltage 100V), the obtained film has excellent ferroelectric performance and energy storage characteristics, and its residual polarization intensity is 3.7μC / cm 2 , saturation polarization intensity 36.3μC / cm 2 , field-induced polarization up to 32.6μC / cm 2 The breakdown field strength is 4.0MV / cm, and the effective energy storage density is as high as 54.2J / cm 3 , the energy storage efficiency is 78.7%.

[0100] Comparative Example 1

[0101] (1) Matrix treatment:

[0102] Select semiconductor substrate Si or Si / SiO2 as the substrate, use acetone and alcohol to ultrasonically clean it to remove oily impurities on the surface, then use deionized water to clean it for the final time, then blow it dry with nitrogen, and finally put it into the vacuum coating chamber, and draw the back vacuum to 2×10 -4 Pa, heated to 300°C;

[0103] (2) Depositing the bottom electrode on the substrate

[0104] A conductive metal target material Ti / Pt is used, and a bottom electrode layer is deposited on the substrate by radio frequency or direct current magnetron sputtering at the temperature of step (1). The atmosphere during deposition is Ar, the Ar gas flow rate is controlled at 39 sccm, the gas pressure is controlled at 0.3 Pa, the target power is 55 W, and the total bottom electrode film thickness is 150 nm.

[0105] (3) Deposition of buffer layer on the bottom electrode

[0106] A LaNiO3 target material with a higher matching degree with tetragonal barium titanate is used, and the temperature is maintained at 200°C to deposit a buffer layer on the substrate by RF or DC magnetron sputtering. The atmosphere during deposition is a mixed gas of Ar and O2, the Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 0.3Pa, the target power is 100W, and the total film thickness of the buffer layer is 100nm.

[0107] (4) Deposition of a barium titanate dielectric layer on the buffer layer

[0108] A ceramic BaTiO3 target is used, and the temperature in step (3) is maintained to deposit a BaTiO3 layer on the bottom electrode by radio frequency magnetron sputtering. The sputtering atmosphere is a mixed gas of Ar and O2. The Ar gas flow rate is controlled at 60sccm, the O2 flow rate is controlled at 15sccm, the gas pressure is controlled at 1.2Pa, the sputtering power of the BaTiO3 target is 100W, and the thickness is 250-350nm.

[0109] (5) Deposition of top electrode on the barium titanate dielectric layer

[0110] Using metal targets, deposition is carried out by RF or DC magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2-5W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

[0111] After electrical performance testing, the ferroelectric loop Fig. 9 As shown. After electrical testing (voltage 100V), the obtained film has excellent ferroelectric properties and energy storage characteristics, and its residual polarization strength is 3.8μC / cm 2 , saturation polarization intensity 37.5μC / cm 2 , field-induced polarization up to 33.7μC / cm 2 The breakdown field strength is 2.8MV / cm, and the effective energy storage density is as high as 42.2J / cm 3 , the energy storage efficiency is 76.9%.

[0112] The BaTiO3 films prepared in Examples 1-3 and Comparative Example 1 were analyzed by XRD, GIXD and TEM, respectively, and the film structure was nano-columnar crystals.

[0113] Figure 5The dielectric constant (a) and loss tangent (b) of the barium titanate film prepared in the embodiment of the present invention illustrate that the dielectric constant increases with the thickness of the LNO layer until the thickness reaches 50nm. Among them, at 1kHz, the dielectric constant of BTO / LNO-0 is about 64, BTO / LNO-25 is about 85, and the dielectric constant of BTO / LNO-50 is the largest, about 164. With the further increase of LNO thickness, the dielectric constant of BTO / LNO-100 decreases to about 124. In addition, in the measurement frequency range of [1kHz, 1MHz], the dielectric constants of all BTO films show weak frequency dependence, indicating that the polarization relaxation related to the interface and body charge carriers is not significant. Except near the high-frequency end, the dielectric loss of the BTO film is relatively low and flat. For example, the tanδ of the BTO / LNO-50 film at 1kHz is about 0.037, which increases to 0.046 at 100kHz and finally increases to only 0.083 at 1MHz. Therefore, the large dielectric constant and low dielectric loss of the BTO / LNO-50 film ensure its excellent charging and energy storage performance.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a BaTiO3 ferroelectric thin film with high energy storage at low temperature, characterized in that: The method comprises the following steps: substrate processing, depositing a bottom electrode on the substrate, depositing a buffer layer on the bottom electrode, depositing a barium titanate dielectric layer on the buffer layer, and depositing a top electrode on the barium titanate dielectric layer; Depositing a buffer layer on the bottom electrode comprises the following steps: using a LaNiO3 target material, maintaining the temperature at 195-205°C to deposit the buffer layer on the substrate by radio frequency or direct current magnetron sputtering; The total film thickness of the buffer layer is 0 to 50 nm.

2. The preparation method according to claim 1, characterized in that: The temperature for depositing the buffer layer is 200° C.; the total film thickness of the buffer layer is 25 to 50 nm.

3. The preparation method according to claim 1, characterized in that: The substrate treatment includes the following steps: selecting a semiconductor substrate Si or Si / SiO2 as the substrate, ultrasonically cleaning it with an ultrasonic detergent, removing the ultrasonic detergent with water, then drying it with an inert gas, and finally placing it in a vacuum coating chamber to evacuate; Preferably, the ultrasonic detergent is acetone, alcohol or a mixture of the two; Preferably, the vacuum coating chamber comprises the following steps: the backing vacuum is pumped to 1.9×10 -4 -2×10 -4 Pa, heated to 290-300℃.

4. The preparation method according to claim 1, characterized in that: Depositing the bottom electrode on the substrate comprises the following steps: using a conductive metal target material Ti / Pt, depositing a bottom electrode layer on the substrate by radio frequency or direct current magnetron sputtering at a substrate treatment process temperature; Preferably, the atmosphere during deposition is Ar; Preferably, the Ar gas flow rate is controlled at 35-40 sccm; Preferably, the air pressure is controlled at 0.3-0.35Pa; Preferably, the target power is 50-55W; Preferably, the total thickness of the bottom electrode is 100-150nm 。 5. The preparation method according to claim 1, characterized in that: During the process of depositing the buffer layer on the bottom electrode, the atmosphere during deposition is a mixed gas of Ar and O2; Preferably, the gas pressure of the deposited buffer layer is controlled to be ≤0.3Pa; Preferably, the Ar gas flow rate is controlled at 50-60 sccm, and the O2 flow rate is controlled at 15-20 sccm; Preferably, the target power is 90-100W.

6. The preparation method according to claim 1, characterized in that: Depositing a barium titanate dielectric layer on the buffer layer comprises the following steps: using a ceramic BaTiO3 target and maintaining a temperature for depositing the buffer layer to deposit a BaTiO3 layer on the buffer layer by radio frequency magnetron sputtering; Preferably, the gas pressure for depositing the barium titanate dielectric layer is ≥1.2 Pa; Preferably, the sputtering atmosphere is a mixed gas of Ar and O2; Preferably, the Ar gas flow rate is controlled at 50-60 sccm, and the O2 flow rate is controlled at 15-20 sccm; Preferably, the sputtering power of the BaTiO3 target is 100W; Preferably, the thickness is 250nm to 350nm.

7. The preparation method according to claim 1, characterized in that: Depositing the top electrode on the barium titanate dielectric layer includes the following steps: using a metal target, depositing by radio frequency or direct current magnetron sputtering at room temperature, the sputtering atmosphere is air, and the target power density is 2 to 5 W / cm 2 , the diameter of the upper electrode is controlled between 200μm and 1000μm.

8. A BaTiO3 ferroelectric film with high energy storage at low temperature, prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the BaTiO3 ferroelectric thin film with high energy storage at low temperature according to claim 8 in energy storage.

10. The use according to claim 9, characterized in that: The energy storage applications include electronic chips or integrated devices.